Generative AI, practical reason, and Law: Can generative language models perform genuine practical reasoning? - Begazo Cáceres, Alonso Ramiro (2025)
Artificial intelligence models, especially language-generating ones, have burst onto the academic scene with great intensity. These models allow interaction with a system trained to algorithmically construct responses within a dialectical dynamic, allowing us to answer questions not only of a conceptual nature but also of a problem-solving nature for various types of problems.In this article, from the perspective of practical reasonableness with Aristotelian roots, we will argue why this tool, which presents itself as “intelligent,” is incapable of carrying out true practical reasoning processes to guide action due to its lack of rational properties, especially in those areas governing human behavior linked to the legal rights that constitute law.